Strategies to increase physician engagement in acute care settings: a scoping review. Issue 7 (7th November 2019) - Shaw, Graham; Smith, Neale; Khowaja, Asif; Mitton, Craig; Denis, Jean-Louis; Lovato, Chris
Abstract : Purpose: Despite growing attention to physician engagement there is a lack of literature to guide the development of physician-led interventions. A scoping review was conducted to describe physician-led strategies that have been implemented to promote increased physician engagement in acute care settings. Strategies are viewed through the theoretical lens of institutional work to advance the understanding about how the theory can be applied. The paper aims to discuss this issue. Design/methodology/approach: Searches were conducted in English-language publications (2012–2017). Of 35 retained articles, 15 were from the gray literature; and 20 were peer reviewed. The review was guided by Arskey and O'Malley's (2005) five-stage process. Findings: Five themes reflecting different foci of physician-led activity were examined from the perspective of institutional work: systematically analyze context using participatory methods; work collaboratively toward locally defined, shared targets and build in processes to monitor progress; expand physicians' role and capacity to include leadership toward shared organizational goals; promote appropriate rewards and incentives for work that builds engagement; and invest in opportunities for formal and informal communication and interaction. Practical implications: Physicians considering action to increase their engagement in system improvement may benefit from analysis of local opportunities and barriers in selecting context-relevant activities that will motivate participation and build engagement through a balance of institutional work. Originality/value: The paper considers the potential for physicians to initiate and support activity that will increase their engagement. It provides pragmatic strategies for designing intervention and research using the theoretical lens of institutional work.